Optimization of the Use of Farm Waste and Water Hyacinth for Earthworm (Lumbricus rubellus) Cultivation Media - Ulan Paluti Agustina; Agus Prasetya; Ambar Pertiwiningrum (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
This study aimed to determine the effect of water hyacinth addition to farm waste on the number of earthworms, earthworm weight, media shrinkage, vermicompost quality, and the sustainability and sensitivity of earthworm farming. The study was prepared using a completely randomized design with two different factors, the water hyacinth (media without water hyacinth and media with 5% water hyacinth addition) and raw materials from farm waste (chicken and cow manure, and biogas sludge from chicken and cow manure), with three replications for each treatment. The results showed that the addition of water hyacinth to raw materials from farm waste had a very significant effect on the number of earthworms, earthworm weight, media shrinkage, vermicompost quality (except for P2O5 level that had no significant increase). When manure is to be added to the cultivation media, it is recommended to use cow manure, while both types of biogas sludge (from chicken and cow manure) are good for the cultivation of earthworm. Based on the study of sustainability, the use of farm waste and water hyacinth as media to raise earthworm gives a positive value in economic and environmental aspects. Therefore, it has great potential.